Spiritual Development in Religious Nonprofit Organizations: The Integration of Professional Human Resource Management - Waldan, Raziki; Juliana, Diena (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2026)
This study examines the integration of professional human resource management (HRM) and spiritual development within a religious nonprofit organization. Using a qualitative case study approach, the research was conducted at Masjid Ismuhu Yahya, Pontianak, Indonesia. Data were collected through in-depth interviews, direct observation, and document analysis involving mosque leaders, human resource managers, entrusted students, and staff members. The findings reveal that Masjid Ismuhu Yahya has implemented competency-based recruitment, structured training, and clear human resource classification aligned with professional HRM principles, while simultaneously embedding systematic spiritual development through religious routines and residential spiritual programs. This integration fosters human resources who are not only professionally competent but also possess strong spiritual values, integrity, and commitment. The study concludes that harmonizing professional HRM with spiritual development enhances organizational effectiveness, sustainability, and value-based identity. These findings contribute to the literature on human resource management in religious nonprofit organizations and offer practical insights for faith-based institutions seeking to balance professionalism and spirituality.